2020
DOI: 10.5829/ije.2020.33.04a.22
|View full text |Cite
|
Sign up to set email alerts
|

Developments Made in the Field of Drilling Fluids by Saint Petersburg Mining University

Abstract: The article discusses researches performed in the Well Drilling Department of the St. Petersburg Mining University. The directions of development of the department are shown. Special attention in this article is paid to research in the field of developing drilling fluids for drilling wells in various mining and geological conditions. It is shown that the gas-liquid mixtures studied by the department will be effective for under balanced drilling under conditions of abnormally low reservoir pressures when using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…In general, the reach of a boom in modern harvesting machines is up to 10 meters. Thus, their operating range, i.e., the areas between the skidding trails on which the machines can effectively use the boom, is almost 20 m. Similar conclusions are drawn by other researchers [11,18].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In general, the reach of a boom in modern harvesting machines is up to 10 meters. Thus, their operating range, i.e., the areas between the skidding trails on which the machines can effectively use the boom, is almost 20 m. Similar conclusions are drawn by other researchers [11,18].…”
Section: Resultssupporting
confidence: 86%
“…However, wider spacing would increase the cleaning costs. Frutig et al [18] found that a wider interval (optimum: 30-50 m) is advisable in the long-term perspective, as losses due to slower growth and less valuable wood are of great importance in calculating the entire turnover period. This conclusion coincides with the results obtained in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Natural gas hydrates are ice-like crystalline that is formed by water and gas molecules at low temperature and high pressure [1][2][3]. Some investigations found that organic carbon stored in gas hydrates is about twice as much that in conventional fossil energy sources [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…During maintenance, according to the actual state, some parameters are monitored, and on this basis, it is determined whether equipment repair is necessary or not. This method of maintenance is the most preferred because repairs are carried out only when necessary [8].…”
Section: Introductionmentioning
confidence: 99%